Parametric Studi Desain Kapal Patroli Fiber Reinforced Plastic untuk Perawatan Lampu Approach Bandara di Kepulauan Natuna - Naufal Salehtra Ghalib; Mardi Santoso; Aang Wahidin (Politeknik Perkapalan Negeri Surabaya, 2023)
The condition of Indonesia as an island nation that has many islands with potential for tourismand investment in the field of natural resources is abundant. The construction of airports in the islandsis an effort to support this potential, but due to limited land, some airport equipment that is importantand not eliminable is placed in the water area. Patrol boats are very important, to assist in airportoperations, especially for maintenance of equipment placed in the waters. So a patrol boat with FRP(Fiberglass Reinforced Plastic) material was designed. From the research conducted, the ship is designedto have a speed of 20 knots with the main size of the ship, namely 13 meters long, 3.6 meters wide, 1.5meters high, 0.6 meters of water level obtained from the ratio comparison of existing comparison ships.From modeling using the size of the ship that has been obtained, the linesplan as found Picture 2, andthe general plan as found in Picture 8 are also obtained after the calculation stages. The patrol boat isdesigned using 2 Yanmar 6LY400 engines, with a ZF 115 ATS gearbox and a B5-105 type propeller, fromthe propulsion system the ship can reach a speed of 21.31 knots at 100% engine power. The patrol boatin this study is analyzed for stability with eight conditions where all conditions meet the rules and criteriaof HSC 2000 ANNEX 8.